Dorsal Penile Curvature in Children: A Review - Karabulut, Ramazan; Turkyilmaz, Zafer; Kaya , Cem; Türker, Leyla Nur; Atan, Ali; Sonmez, Kaan (Urology Journal, 2025)
Purpose: To review the current literature on dorsal penile curvature (DPC) in children, including its etiology, diagnosis, and principles of treatment. Materials and Methods: A literature review was conducted on DPC in children, focusing on its etiology (e.g., skin tethering, corporal disproportion), association with other conditions such as hypospadias and epispadias, and surgical treatment methods. Results: DPC is a rare condition, often associated with neonatal circumcision, hypospadias, or epispadias. The etiology includes skin ties, fibrotic tissues, and asymmetric corporal development. Spontaneous resolution can occur, especially in cases following circumcision. Surgical correction is typically considered for curvatures of 30° or greater that are functionally concerning. Common surgical techniques include ventral plication, wedge resection (Nesbit procedure), and grafting. Conclusion: While mild DPC often requires no intervention, surgical correction should be considered for significant curvatures (≥ 30°) to prevent future functional issues. Cases that develop after neonatal circumcision may resolve spontaneously.